Multiwalled carbon nanotubes with molybdenum dioxide nanoplugs--new chemical nanoarchitectures by electrochemical modification. - Jurkschat, K; Wilkins, S; Salter, C; Leventis, H; Wildgoose, G; Jiang, L; Jones, T; Crossley, A; Compton, R (2006)
The electrochemical modification of the equivalent edge-plane-like sites on multiwalled carbon nanotubes (MWCNT) to produce nanoplugs of molybdenum dioxide (MoO2) was analyzed. The electrochemical deposition was performed using experimental conditions, where the deposition time was varied from 0.1 to 10.0 s. It was found that it can be possible to form nanorings of MoO 2 around the circumference of the nanotube. The results show that the molybdenum metal at the ends of the CNTs can be used to form well-defined electrical contacts between CNTs.